2001
DOI: 10.1111/1467-8624.00294
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Adolescents' Prosocial Moral Judgment and Behavior: Relations to Sympathy, Perspective Taking, Gender‐Role Orientation, and Demographic Characteristics

Abstract: The goal of this study was to examine demographic and individual difference variables that predict level of prosocial moral judgment and self-reported prosocial behavior and to test mediating or moderating relations among predictors. The relations of prosocial moral reasoning and self-reported prosocial behavior to perspective taking, sympathy, age, sociometric status, and gender-role orientation were examined with a sample of 149 Brazilian adolescents who completed a series of questionnaire measures. Prosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
165
0
26

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(207 citation statements)
references
References 50 publications
16
165
0
26
Order By: Relevance
“…Además, el razonamiento moral prosocial suele estar acorde con los valores morales y con la jerarquía, que dirige la conducta de ayudar, de ahí que se espere que contribuya a consolidar las características personales prosociales (Eisenberg, Hofer, Sulik y Liew, 2014). De este modo, el razonamiento moral prosocial se relaciona con conductas prosociales o acciones destinadas a beneficiar al otro (Carlo et al, 2010;Eisenberg, Zhou y Koller, 2001) y se vincula a ciertas emociones morales, como la empatía emocional (Eisenberg, Fabes y Spinrad, 2006;Malti y Keller, 2009). Por el contrario, el razonamiento moral prosocial se relaciona negativamente con razonamiento hedonista en adolescentes (Eisenberg, Carlo, Murphy y Van Court, 1995) y con la conducta agresiva (Carlo et al, 2013).…”
Section: Razonamiento Moral Prosocialunclassified
“…Además, el razonamiento moral prosocial suele estar acorde con los valores morales y con la jerarquía, que dirige la conducta de ayudar, de ahí que se espere que contribuya a consolidar las características personales prosociales (Eisenberg, Hofer, Sulik y Liew, 2014). De este modo, el razonamiento moral prosocial se relaciona con conductas prosociales o acciones destinadas a beneficiar al otro (Carlo et al, 2010;Eisenberg, Zhou y Koller, 2001) y se vincula a ciertas emociones morales, como la empatía emocional (Eisenberg, Fabes y Spinrad, 2006;Malti y Keller, 2009). Por el contrario, el razonamiento moral prosocial se relaciona negativamente con razonamiento hedonista en adolescentes (Eisenberg, Carlo, Murphy y Van Court, 1995) y con la conducta agresiva (Carlo et al, 2013).…”
Section: Razonamiento Moral Prosocialunclassified
“…Perspective taking allows one to develop a sense of sympathy for others and its development is often correlated with one's emotional regulation and prosocial behavior (e.g., Carlo et al, 2003;Eisenberg, Zhou, & Koller, 2001). Hoglund (2005) also found that individual differences are apparent in the level of social-cognitive capabilities (perspective taking and interpersonal skills) amongst victimized children.…”
Section: The Role Of Emotional Regulationmentioning
confidence: 99%
“…These results are confirmed if processes are not simply analysed on the basis of gender but if the orientation of the gender role is also evaluated. Thus, a female orientation is predictive of greater empathy both as concern for the other and as perspective taking (Carlo, Koller, Eisenberg, Silva, & Frohlich, 1996;Eisenberg, Zhou, & Koller, 2001) and predictive of less criminal behaviours in adolescents with this type of orientation (Keung Ma, 2005).…”
mentioning
confidence: 99%